Diseño del sistema de acondicionamiento de aire para las oficinas administrativas del edificio municipal de Corredores - Sanchún-Varela, Andrea (Instituto Tecnológico de Costa Rica, 2018)
Corredores canton, located in Puntarenas generally presents very high and uncomfortable temperatures to work in an office. Due to this, the main purpose of this project is the design of an air conditioning system of the administrative offices at the municipal building of Corredores, which has a problematic that consists on the decrease of workers’ productivity. This design attends to a direct expansion system of variable refrigerant flow technology with a wired central controller consisting in the determination of the adequate thermal load, the comparison of the selected system between others, the selection of the indoor and outdoor units made with Lennox’ VRF Selector, the making of mechanical drawings, calculation of the project’s financial proposal, and the preparation of the equipment’s maintenance schedule. The whole project was designed following the ASHRAE standards as shown in 6th appendix. After designing it, it was determined that the requested thermal load of the system is 40 tons of refrigeration. Also, the best system option to supply municipal’s building necessities was the VRF technology because after coming up with the financial proposal and comparing it between inverter direct expansion and chilled systems using air-cooled chiller; the result was a savings generated of $134 070 (₡77 626 809) in 5 years using VRF compared to the rest.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Aire; Volumen; Refrigerantes; Variables; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Mechanical and thermal engineering